Fungi Associated with the Quince Borer, C oryphodema tristis (Drury) (Lepidoptera: Cossidae), in Grapevines - Hoppner, G.F.J.; Ferreira, J.H.S. (South African Journal of Enology and Viticulture, 2017)
Fungal discolouration of wood was found associated with galleries of Coryphodema tristis in grapevines. The mean percentage damage caused by larvae and fungal discolouration was 14,8 % and 13,5 % respectively. Twelve fungal species were isolated from the discoloured region. None of these fungi were transmitted from one generation of the insect to the next.